Bizarre leiomyoma of the scrotum: A case report and review of the literature - SU, ZHENGMING (D.A. Spandidos, 2014)
Bizarre leiomyomas of the scrotum are rare benign tumors that are often misdiagnosed. In this study, we present a case of bizarre leiomyoma of the scrotum in a 53-year-old male. The patient presented with a painless scrotal mass that was insidious in the right side of the scrotum with no sudden increase in size. Definitive preoperative diagnosis could not be established; however, following surgical resection of the tumor, a diagnosis of bizarre leiomyoma of the scrotum was determined by pathological examination. The patient was followed up six months following resection and no problems were reported. This is the first reported case of bizarre leiomyoma of the scrotum in China. A supplementary review of previously published cases and literature is also presented.